2018
DOI: 10.1248/bpb.b17-00655
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of 3,5,2′,4′-Tetrahydroxychalcone on Production of Uric Acid in Hypoxanthine-Induced Hyperuricemic Mice

Abstract: The mechanism of 3,5,2′,4′-tetrahydroxychalcone on lowing urate level is still unknown. Here we investigated the effects of 3,5,2′,4′-tetrahydroxychalcone on urate levels, xanthine oxidase/xanthine dehydrogenase (XOD/XDH) activities in hypoxanthine-induced hyperuricemic mice, as well as the effects of 3,5,2′,4′-tetrahydroxychalcone on the mRNA expression levels and content of phosphoribosyl pyrophosphate synthetase (PRPS), phosphoribosyl pyrophosphate amidotransferase (PRPPAT) and hypoxanthine-guanine phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…e chalcone scaffold, found in many naturally occurring compounds, have a wide range of bioactive properties and have also been prepared by synthesis [48,49]. As an example, Li and co-workers [50][51][52] prepared several chalcones and evaluated their XO inhibitory activity. Of these, 3,5,2′,4′-tetrahydroxychalcone ( Figure 15 an interesting XO inhibition in a competitive manner, and IC 50 and K i values of 22.5 and 17.4 μM, respectively, were determined [52].…”
Section: Phenolic Compounds and Analoguesmentioning
confidence: 99%
See 3 more Smart Citations
“…e chalcone scaffold, found in many naturally occurring compounds, have a wide range of bioactive properties and have also been prepared by synthesis [48,49]. As an example, Li and co-workers [50][51][52] prepared several chalcones and evaluated their XO inhibitory activity. Of these, 3,5,2′,4′-tetrahydroxychalcone ( Figure 15 an interesting XO inhibition in a competitive manner, and IC 50 and K i values of 22.5 and 17.4 μM, respectively, were determined [52].…”
Section: Phenolic Compounds and Analoguesmentioning
confidence: 99%
“…e best effect occurred with doses between 2 and 4 mg/kg [50][51][52]. Studies performed by the authors suggested that this chalcone act by a dual mechanism [50].…”
Section: Phenolic Compounds and Analoguesmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these key enzymes, XO is the most commonly studied enzyme. 3,5,2′,4′-tetrahydroxychalcone significantly inhibits the activities of XO in liver, and the decreased content of PRPP in liver will suppresse the UA production (Niu et al, 2018). In our review, nearly half of the studies (83/186, 45%) confirm that herbs regulate XO synthesis and activity.…”
Section: Herbs Lower Serum Uric Acid By Targeting Uric Acid Synthesismentioning
confidence: 65%